2023
DOI: 10.18280/ijepm.080101
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Political Risk on the Economic Efficiency of Russian Renewable Energy Projects

Abstract: This article is the second of the author's works devoted to a comprehensive study of the economic efficiency of Russian renewable energy (RE) projects. The main goal of this paper is to study the level of influence of political risk on the economic efficiency of RE projects that are implemented in the Russian energy market using a state support program. Fifty-two solar, wind and small hydropower projects, which have received support in the form of a capacity-based support scheme in 2018-2020, were selected as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As a result of the study, it was found that technological innovation plays an important role in the clean energy-growth link. The degree of political risk and its effect on the economic viability of renewable energy projects using a state assistance program in the Russian energy market were examined by Chebotareva [28].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, it was found that technological innovation plays an important role in the clean energy-growth link. The degree of political risk and its effect on the economic viability of renewable energy projects using a state assistance program in the Russian energy market were examined by Chebotareva [28].…”
Section: Introductionmentioning
confidence: 99%
“…Their selection is due to the experience accumulated to date in risk management in renewable energy projects. For example, the influence of political risks on the implementation of renewable energy projects is studied in [40][41][42][43][44][45], environmental risks in [44,[46][47][48][49][50], and economic risks in [51][52][53][54][55][56]. The general methodology of our study is presented in the form of the block diagram depicted in Figure 1, which follows.…”
Section: Introductionmentioning
confidence: 99%